Epidermal Inclusion Cyst of Male Breast Following Traumatic Implantation - Haque, MM; Mamun, MA; Rahman, MA; Nesa, Meherun; Badruddoza, SM (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Epidermal Inclusion cyst of male breast is a rare condition as reported in the literatures. We had a young male patient who presented with a recurrent breast lump. This case had a number of conflicting diagnostic movements before being confirmed by histopathological examination of the excised lump to be Epidermal Inclusion cyst. The patient was found to be healthy at follow up after three months DOI: http://dx.doi.org/10.3329/jbcps.v30i2.11411 J Bangladesh Coll Phys Surg 2012; 30: 96-97